2016
DOI: 10.1016/j.ghir.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Humanin: Functional Interfaces with IGF-I

Abstract: Humanin is the first newly discovered peptide encoded in the mitochondrial genome in over three decades. It is the first member of a novel class of mitochondrial derived peptides. This small, 24 amino acid peptide was initially discovered to have neuroprotective effects and subsequent experiments have shown that it is beneficial in a diverse number of disease models including stroke, cardiovascular disease, and cancer. Over a decade ago, our lab found that humanin bound IGFBP-3 and more recent studies have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 77 publications
2
38
0
4
Order By: Relevance
“…Humanin is secreted from cells and thus humanin is detected in both conditioned medium and plasma [7, 8]. The plasma levels of humanin decline with age in mice and humans [9] and their levels are positively correlated with longevity in mouse models [10]. The long-lived Ames dwarf mice have a 50% increase in circulating humanin levels, whereas the short-lived GH-transgenic mice have lower levels [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Humanin is secreted from cells and thus humanin is detected in both conditioned medium and plasma [7, 8]. The plasma levels of humanin decline with age in mice and humans [9] and their levels are positively correlated with longevity in mouse models [10]. The long-lived Ames dwarf mice have a 50% increase in circulating humanin levels, whereas the short-lived GH-transgenic mice have lower levels [1113].…”
Section: Introductionmentioning
confidence: 99%
“…1). The characteristics of the variant amino acids revealed a functional pattern that was also noted in a previous studies [225,247]. The region between proline 3 to proline 19 was described as the "core domain" of humanin that is essential for the secretion of the full-length peptide from the cell despite the wide variability at position 3 between species.…”
Section: S-humanin and Sequence Homologysupporting
confidence: 69%
“…Residues 3-19 have also been described as the "core domain" of the peptide and are responsible for its neuroprotective activity [224]. Modification of core domain amino acids was found to yield analogues resulting in increased potency, affect binding to growth-factor binding proteins, as well as affect its own secretion [225].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that in addition to the above mentioned 37 genes, the mitochondrial chromosome also encodes multiple biologically active peptides derived from small open reading frames (ORF) 1519 . We discovered one such mitochondrial derived peptide (MDP) encoded from the 12S rRNA in the mtDNA called m itochondrial o pen-reading-frame of the twelve S rRNA – c (MOTS-c) 20 .…”
Section: Introductionmentioning
confidence: 99%